Basic Sciences of Nuclear Medicine - Khalil, Magdy M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Nuclear medicine has become an ever-changing and expanding diagnostic and therapeutic medical profession. The day-to-day innovations seen in the field are, in great part, due to the integration of many scientific bases with complex technologic advances. The aim of this reference book, Basic Sciences of Nuclear Medicine, is to provide the reader with a comprehensive and detailed discussion of the scientific bases of nuclear medicine, covering the different topics and concepts that underlie many of the investigations and procedures performed in the field. Topics include radiation and nuclear physics, Tc-99m chemistry, single-photon radiopharmaceuticals and PET chemistry, radiobiology and radiation dosimetry, image processing, image reconstruction, quantitative SPECT imaging, quantitative cardiac SPECT, small animal imaging (including multimodality hybrid imaging, e.g., PET/CT, SPECT/CT, and PET/MRI), compartmental modeling, and tracer kinetics.
Medical statistics -- Basic physics of nuclear medicine: Radiation physics -- Interaction of radiation with matter -- Radiochemistry and radiopharmaceuticals: production of radionuclides -- Technetium radiopharmaceuticals -- Iodinated radiopharmaceuticals -- Radionuclides used for therapy -- Quality control of radiopharmaceuticals -- PET radiopharmaceuticals -- Radiation detection instruments -- Radiation dosimetry: Definitions and basic quantities -- Radiation dosimetry: Formulations, models, and measurements -- Radiobiology: Concepts and basic principles -- Image display and processing -- Gamma camera: Basic principles and performance characteristics -- Single photon emission computed tomography (SPECT) -- SPECT degrading factors -- Quantitative cardiac SPECT -- SPECT/CT hybrid imaging -- PET imaging -- PET/CT hybrid imaging -- Tracer kinetic modeling: Basics, concepts, and applications -- Small animal imaging -- Imaging informatics.
Keywords: Medicine; Nuclear medicine; Medicine & Public Health; Nuclear Medicine